Kajian Pustaka Pengaruh Penambahan Dinding Bata Terhadap Kapasitas Beban Lateral Pada Portal Struktur Beton Bertulang - Putri , T.Sy.Zahiyyah Aini Wanda; Ridwan, Ridwan (Dept. of Civil Engineering Universitas Riau, 2023)
This study aims to investigate the impact of masonry infill walls on the behavior of reinforced concrete frames under seismic loads. Traditionally, masonry walls have been considered non-structural elements; however, their interaction with the overall structural behavior is crucial, especially in earthquake-prone areas. Understanding how these walls affect structural performance is essential to ensuring safety and effectiveness in design. This study employs a comprehensive literature review to analyze various factors influencing the performance of masonry walls in reinforced concrete structures. The key aspects examined include material properties, lateral load capacity, energy dissipation ability, and structural deformation. An evaluation is conducted on experimental test results from previous research. The findings reveal that the addition of masonry infill walls significantly increases the lateral stiffness and load-bearing capacity of reinforced concrete frames. Specifically, the study shows that structures with solid masonry walls exhibit a base shear force 1.2 times greater than those with clay brick walls. However, the study also highlights the reduction in deformation due to the brittle nature of masonry, which can lead to shear failure under ultimate load conditions.